Hubungan Status ASI Eksklusif dan Pemberian Kolostrum dengan Kejadian Autisme pada Anak di Bawah 10 tahun - Khaerina, Umi; Herini, Siti; Ismail, Djauhar (JURNAL KESEHATAN REPRODUKSI, 2019)
Background: The cause of autism until now is still not exactly known. One of the efforts in preventing the occurrence of autism is intervention early with giving colostrum and exclusive breastfeeding. The number of autism in Indonesia according to data released by the Central Bureau of Statistics in 2010 was estimated at 2.4 million people. Based on data from autism special school Bina Anggita Yogyakarta, recorded increase in the number of students from the beginning of the school in 2001 were 15 students, in 2009 the number increased to 32 students and in 2013 were 45 students.Objective: To determine the relationship between the status of exclusive breastfeeding and giving colostrum to the incidence of autism in children under 10 years.Methods: This research is a quantitative study with a matched case control study design. Subjects were children aged under 10 years who consisted of children with autism were 19 cases and 19 controls for normal children in Yogyakarta. The independent variable in this study in the provision of colostrum and exclusive breastfeeding, and dependent variable was autism. The counfounding variables are gastrointestinal infections, low birth weight and maternal age. Retrieval of data collected using a questionnaire. Univariable data analysis using frequency distribution, bivariate statistics using the McNemar test, multivariable analysis was not performed because the bivariate analysis, all variables are not significantly.Results: Of the five variables that were related to the occurrence of autism, five variables are not statistically significant and two variables that increase the risk of autism gastrointestinal infection (p=0,09 OR 3,5 CI 95%; 0,66-34,53) and low birth weight (p=0,17 OR 4 CI 95%; 0,39-196,9).Conclusions: There was no significant relationship between the giving of colostrum, exclusive breastfeeding and maternal age, but clinical gastrointestinal infection and low birth weight were risk factor Â of autism.Â Keywords: Colostrum, exclusive breastfeeding, autism.